Book Scavenger - Jennifer Chambliss Bertman (New York Square Fish, 2015)
Twelve-year-old Emily is on the move again. Her family is relocating to San Francisco, home of her literary idol: Garrison Griswold, creator of Book Scavenger, a game where books are hidden and clues to find them are revealed through puzzles. But Emily soon learns that Griswold has been attacked, derailing the launch of his epic new game. Then she and her friend James discover an odd clue, which eventually leads them to a valuable prize. But there are others on the hunt for this special prize, and Emily and James must race to solve the puzzles Griswold left behind before his attackers come after them.
Keywords: Mystery - Suspense -- Mystery - Suspense